Physiotherapists absorption of their professional work - Stychno, Ewa; Czapla, Piotr; Kulczycka, Kinga (Journal of Education, Health and Sport, 2017)
Introduction Absorption of professional work is often perceived intuitively as a zeal for work. High preoccupation with work is referred to as workaholism. Spence and Robbins describe a workaholic as the person who „is highly engaged with work, feels obligated or forced to work because of internal pressure and feels less satisfied with work”. Aim The aim of the study was to evaluate physiotherapists’ absorption of their professional work. Material and methods Two tools were used for the study: the Scale of Being Absorbed by Work – SZAP Golińska and Occupational Stress Scale PMI. The study was conducted in a group of 111 subjects (70 women, 41 men, aged 20-50) Results It has been shown high level of work absorption concerned 15% of physiotherapists (17 persons) average level concerned 77% of respondents (86 persons), low level concerned 7% of respondents (8 persons). Conclusions Workaholism, in the profession of physiotherapist, refers more often to men than to women. The most preoccupied are physiotherapists aged 31-40. High preoccupation negatively affects relationships with friends and family of physiotherapists. More preoccupied with work physiotherapists more often neglect their hobbies than less absorbed. With the increase in work absorption occupational stress is also increasing among physiotherapists in all aspects of stress (general stress, stress resulting from interpersonal and communication stress, work-house stress, work-related stress).